N-terminal domain influences steroid activation of the Atlantic sea lamprey corticoid receptor. Issue 228 (April 2023) - Katsu, Yoshinao; Lin, Xiaozhi; Ji, Ruigeng; Chen, Ze; Kamisaka, Yui; Bamba, Koto; Baker, Michael E.
Abstract: Lampreys are jawless fish that evolved about 550 million years ago at the base of the vertebrate line. Modern lampreys contain a corticoid receptor (CR), the common ancestor of the glucocorticoid receptor (GR) and mineralocorticoid receptor (MR), which first appear in cartilaginous fish, such as sharks. Until recently, 344 amino acids at the amino terminus of adult lamprey CR were not present in the lamprey CR sequence in GenBank. A search of the recently sequenced lamprey germline genome identified two CR sequences, CR1 and CR2, containing the 344 previously un-identified amino acids. CR1 also contains a novel four amino acid insertion in the DNA-binding domain (DBD). We studied corticosteroid and progesterone activation of CR1 and CR2 and found their strongest response was to 11-deoxycorticosterone and 11-deoxycortisol, the two circulating corticosteroids in lamprey. Based on steroid specificity, both CRs are close to elephant shark MR and distant from elephant shark GR. HEK293 cells that were transfected with full-length CR1 or CR2 and the MMTV promoter have about 3-fold higher steroid-mediated activation compared to HEK293 cells transfected with these CRs and the TAT3 promoter. Deletion of the amino-terminal domain (NTD) of lamprey CR1 and CR2 to form truncated CRs decreased transcriptional activation by about 70% in HEK293 cells that were transfected with MMTV, but increased transcription by about 6-fold in cells transfected with TAT3. This indicated that the promoter has an important effect on NTD regulation of transcriptional activation of the CR by steroids. Our results also indicate that the entire lamprey CR sequence is needed for an accurate determination of steroid-mediated transcription. Highlights: Lamprey contains two corticoid receptors (CRs), CR1 and CR2. The N-terminal Domain: an allosteric regulator of transcription for both CRs. 11-deoxycortisol and 11-deoxycorticosterone activate both CRs. Lamprey CR is closer to elephant shark MR than to elephant shark GR.